Skin game : a novel of the Dresden files - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files., 2014)
Chicago wizard Harry Dresden must help a hated enemy, Nicodemus Archleone, break into a high security vault to steal something belonging to the Lord of the Underworld.